Participatory Methods in the Education of Architects (EAAE Annual Conference Proceedings, 2023)
To understand the context, from the physical through the sociological to the economic, the architect must conduct field research. For a long time, that primarily meant a tour of the location, but recently, the importance of collecting the opinions of all actors of spatial development is becoming highly recognized. Roughly speaking, these are four groups: the local government members; various expert groups representatives; representatives of companies interested in investment and development; and specific or future potential users. Moderating the conversation of all these groups representatives is a demanding yet rewarding task.